Enhanced protein–protein interaction network construction promoted by in vivo cross-linking with acid-cleavable click-chemistry enrichment - Zhao, Lili; Zhong, Bowen; An, Yuxin; Zhang, Weijie; Gao, Hang; Zhang, Xiaodan; Liang, Zhen; Zhang, Yukui; Zhao, Qun; Zhang, Lihua (Frontiers in Chemistry, 2022)
Chemical cross-linking coupled with mass spectrometry has emerged as a powerful strategy which enables global profiling of protein interactome with direct interaction interfaces in complex biological systems. The alkyne-tagged enrichable cross-linkers are preferred to improve the coverage of low-abundance cross-linked peptides, combined with click chemistry for biotin conjugation to allow the cross-linked peptide enrichment. However, a systematic evaluation on the efficiency of click approaches (protein-based or peptide-based) and diverse cleavable click-chemistry ligands (acid, reduction, and photo) for cross-linked peptide enrichment and release is lacking. Herein, together with in vivo chemical cross-linking by alkyne-tagged cross-linkers, we explored the click-chemistry-based enrichment approaches on protein and peptide levels with three cleavable click-chemistry ligands, respectively. By comparison, the approach of protein-based click-chemistry conjugation with acid-cleavable tags was demonstrated to permit the most cross-linked peptide identification. The advancement of this strategy enhanced the proteome-wide cross-linking analysis, constructing a 5,518-protein–protein-interaction network among 1,871 proteins with widely abundant distribution in cells. Therefore, all these results demonstrated the guideline value of our work for efficient cross-linked peptide enrichment, thus facilitating the in-depth profiling of protein interactome for functional analysis.